Pengaruh Tata Kelola dan Digitalisasi Terhadap Kepatuhan Penerapan PSAK 409 pada BAZNAS di Jawa Timur - zahroh, Saadatus; Priyadi, Ira Hasti (AKTSAR: Jurnal Akuntansi Syariah, 2026)
This study aims to analyze the effect of governance and digitalization on compliance with the implementation of Financial Accounting Standards Statement (PSAK) 109 at the National Zakat Board (BAZNAS) of Pamekasan Regency. Compliance with PSAK 109 is essential to ensure transparent, accountable, and sharia-compliant zakat management. This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to BAZNAS Pamekasan management and analyzed using multiple linear regression. The results indicate that governance and digitalization each have a positive and significant effect on compliance with PSAK 109 implementation. Simultaneously, both variables significantly influence compliance with PSAK 109. These findings provide practical implications for strengthening financial management and zakat fund distribution through improved governance and information technology utilization.